Aegla buenoi n. sp. (Decapoda: Anomura): first record of aeglid crab from Cinzas River basin, Brazil - Marçal, Ingrid Costa; Páez, Fernanda Polli; Souza-Shibatta, Lenice; Sofia, Silvia Helena; Teixeira, Gustavo Monteiro (Zootaxa, 2021)
A new species of freshwater anomuran crab, Aegla buenoi n. sp., is described. The new taxon was collected from two streams within the Cinzas River basin, Paraná state, Brazil. We used morphological and molecular data (COI mtDNA) to distinguish the new species from its congeners. Aegla buenoi n. sp. is differentiated by morphological diagnostic features of the cephalothorax, chelipeds, second abdominal epimeron, and uropods. Molecular results confirm the separation of A. buenoi n. sp. from closely related species (A. castro Schmitt, 1942, A. lata Bond-Buckup & Buckup, 1994, and A. jacutinga Marçal & Teixeira, 2020). Hence, our study increases the known diversity of aeglids and reports the first species of Aegla from the Cinzas River basin.